Acroparesthesia in a Female: Diagnostic Dilemma - Fnu Kelash; Lara Kujtan; Padmaja V. Mallidi (Case Reports in Medicine)
Fabry disease is an X-linked lysosomal storage disorder caused by deficient activity of a-galactosidase A (also known as ceramide trihexosidase) and resultant accumulation of globotriaosylceramide (Gb3) and related glycophospholipids. The disease affects nearly all major organ systems, with the primary sites damaged by Gb3 including renal glomeruli, myocardium, neurons of the dorsal ganglion and autonomic nervous system, and vascular endothelial and smooth muscle. Progressive deposition in these organ systems leads to renal and heart failure; debilitating pain as a result of nervous system involvement also occurs.